Development and evaluation of solid lipid nanoparticles of raloxifene hydrochloride for enhanced bioavailability. - Kushwaha, Anand Kumar; Vuddanda, Parameswara Rao; Karunanidhi, Priyanka; Singh, Sanjay Kumar; Singh, Sanjay (BioMed Research International, 2013)
Raloxifene hydrochloride (RL-HCL) is an orally selective estrogen receptor modulator (SERM) with poor bioavailability of nearly 2% due to its poor aqueous solubility and extensive first pass metabolism. In order to improve the oral bioavailability of raloxifene, raloxifene loaded solid lipid nanoparticles (SLN) have been developed using Compritol 888 ATO as lipid carrier and Pluronic F68 as surfactant. Raloxifene loaded SLN were prepared by solvent emulsification/evaporation method, and different concentrations of surfactant, and homogenization speed were taken as process variables for optimization. SLN were characterized for particle size, zeta potential, entrapment efficiency, surface morphology, and crystallinity of lipid and drug. In vitro drug release studies were performed in phosphate buffer of pH 6.8 using dialysis bag diffusion technique. Particle sizes of all the formulations were in the range of 250 to 1406 nm, and the entrapment efficiency ranges from 55 to 66%. FTIR and DSC studies indicated no interaction between drug and lipid, and the XRD spectrum showed that RL-HCL is in amorphous form in the formulation. In vitro release profiles were biphasic in nature and followed Higuchi model of release kinetics. Pharmacokinetics of raloxifene loaded solid lipid nanoparticles after oral administration to Wistar rats was studied. Bioavailability of RL-HCL loaded SLN was nearly five times than that of pure RL-HCL.